2022
DOI: 10.1038/s41598-022-09353-z
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of interstitial lung disease on the survival of systemic sclerosis with pulmonary arterial hypertension

Abstract: To assess severity markers and outcomes of patients with systemic sclerosis (SSc) with or without pulmonary arterial hypertension (PAH-SSc/non-PAH-SSc), and the impact of interstitial lung disease (ILD) on PAH-SSc. Non-PAH-SSc patients from the Spanish SSc registry and PAH-SSc patients from the Spanish PAH registry were included. A total of 364 PAH-SSc and 1589 non-PAH-SSc patients were included. PAH-SSc patients had worse NYHA-functional class (NYHA-FC), worse forced vital capacity (FVC) (81.2 ± 20.6% vs 93.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Those with PAH-ILD were more likely to have extensive ILD and a lower FVC than those with ILD-only. This is consistent with recent data demonstrating a higher FVC is associated with better survival in PAH-ILD [10]. Interestingly, whilst univariate analyses indicated worse prognosis with increasing ILD severity, our multivariable model suggested that PAH-ILD with limited ILD conferred a better prognosis than extensive ILD-only.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Those with PAH-ILD were more likely to have extensive ILD and a lower FVC than those with ILD-only. This is consistent with recent data demonstrating a higher FVC is associated with better survival in PAH-ILD [10]. Interestingly, whilst univariate analyses indicated worse prognosis with increasing ILD severity, our multivariable model suggested that PAH-ILD with limited ILD conferred a better prognosis than extensive ILD-only.…”
Section: Discussionsupporting
confidence: 92%
“…Limited data exist in the wider literature to describe individuals with SSc who develop concurrent precapillary PH and ILD. We demonstrated a higher proportion of males in the PAH-ILD group which is consistent with other studies [10,12]. In our cohort, people with both PAH-ILD and PAH-only were older at SSc onset; other data suggest that those with PAH-only may be older than those with ILD-associated PH [12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We did not include severe SSc-ILD or patients suffering from severe PAH due to practical issues for the patients. Note that a recent study reports that global survival of PAH-SSc patients was not affected by ILD regardless its severity 22 . Therefore, it is recommended to carry out further research in this line.…”
Section: Discussionmentioning
confidence: 93%